A Practitioner Centred Assessment on Health Information Systems Interoperability Readiness in Zimbabwe: Mixed Study Approach - Prosper Tafadzwa Denhere; Munyaradzi Zhou; Ephias Ruhode (Horizon Research Publishing Corporation, 2023)
Contemporary health information systems have moved to become electronically supported. This has presented the need for these eHealth systems to exist as an ecosystem that allows for healthcare service collaboration amongst service practitioners. In this research paper, the aim is to form an understanding of the healthcare practitioner readiness for Health Information Systems (HIS) interoperability in Zimbabwe. Some qualitative interview and quantitative 5 point Likert scale questionnaires were used to gather the data concurrently before the data were analysed both qualitatively and quantitatively. The HIS interoperability readiness survey was captured from responses made by 71 practitioners. The assessment was aimed at assessing factors which were healthcare practitioner readiness, technological infrastructure ownership readiness, policy readiness, core readiness and financial readiness. The findings presented indicate that healthcare practitioners and patients are ready to exist and function as part of an interoperable HIS although some enabling factors were identified in terms of policies needed to support its existence and functionality. Recommendations towards interoperability of HISs achievement were suggested.